Resource-Advantage Theory in Digital Marketing Capabilities: A Systematic Literature Review and Future Research - Yose Andri; Vidyarini Dwita; Abror Abror; Yunia Wardi (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This article aims to analyze how the literature on digital marketing capabilities explains competitive advantage and to assess the extent to which Resource-Advantage Theory can be used as an integrative lens for understanding the relationships among resources, capabilities, and market outcomes. This study employs a systematic literature review approach following the PRISMA. The review was conducted through descriptive bibliometric analysis and keyword mapping using VOSviewer, based on metadata and abstracts. The findings show a significant increase in publications in 2024-2025, with dominant themes including digital marketing, competitive advantage, business performance, social media, big data/AI, data governance, marketing agility, customer experience, and sustainability. The review also confirms that the resource-based view and dynamic capabilities are the dominant theoretical foundations, whereas Resource-Advantage Theory has not yet been used explicitly. Accordingly, this study proposes a Resource-Advantage process model and a future research agenda that emphasizes innovation, trust, data governance, and sustainability.